2001
DOI: 10.1098/rspb.2000.1426
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive suppression in female Damaraland mole–ratsCryptomys damarensis: dominant control or self–restraint?

Abstract: Colonies of Damaraland mole-rats Cryptomys damarensis exhibit a high reproductive skew. Typically one female breeds and the others are anovulatory. Two models, the dominant control model (DCM) and the self-restraint model (SRM), have been proposed to account for this reproductive suppression. The DCM proposes that suppression is under the control of the dominant breeder and is imposed by mechanisms such as aggression, pheromones and interference with copulation, whereas the SRM does not involve aggression dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 26 publications
5
73
0
1
Order By: Relevance
“…Cortisol assays were performed using a coat-a-count cortisol kit (Diagnostic Products Corporation) that had previously been validated for urinary cortisol monitoring in Damaraland mole-rats (Clarke et al 2001). All samples were assayed in duplicate and the assay sensitivity (determined at 90% binding) was 6.1 ng/ml.…”
Section: Urine Sample Collection and Urinary Cortisol Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…Cortisol assays were performed using a coat-a-count cortisol kit (Diagnostic Products Corporation) that had previously been validated for urinary cortisol monitoring in Damaraland mole-rats (Clarke et al 2001). All samples were assayed in duplicate and the assay sensitivity (determined at 90% binding) was 6.1 ng/ml.…”
Section: Urine Sample Collection and Urinary Cortisol Assaymentioning
confidence: 99%
“…To correct for variation in urinary cortisol concentrations resulting from variation in urine concentration, determinations of creatinine concentrations were also conducted in duplicate for all urine samples (as described by Bonney et al 1982;Clarke et al 2001). The intra-assay coefficient of variation was 3.0%.…”
Section: Urine Sample Collection and Urinary Cortisol Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in red deer (Cervus elaphus) suggest that corpus luteum function is affected by social status [34]. In rodents and monkeys, it has been demonstrated that only dominant females ovulate and inhibit the ovulation in subordinated females through aggression, visual cues and pheromones [35,36]. In ibexes raised in captivity, the social interactions are reinforced and aggression directed towards dominated females (usually with lower bodyweight) has been frequently observed in our study.…”
Section: Discussionmentioning
confidence: 48%
“…Social stress also has been shown to cause a reduction in locomotor activity, social motivation and interactions (Blanchard et al, 2001, Denmark et al, 2010, Sandi and Haller, 2015. In a previous study, Damaraland queens were found to have the lowest or almost the lowest levels of cortisol among the females in the colony, although this difference is not significant in most colonies (Clarke et al, 2001). However, worker mole-rats with the lowest status in the colony shows the largest number of proliferating cells and young neurons and are the most active.…”
Section: Effect Of Social Status On Neurogenesismentioning
confidence: 93%